Apropiacionismos y resignificaciones de la obra “Various small fires” de Ed Ruscha. / Appropriationism and reinterpretations of the artwork “Various small fires” of Ed Ruscha - Mínguez García, Hortensia (Tercio Creciente, 2017)
Durante más de cincuenta años, los libros de artista de Ed Ruscha han favorecido una particular tendencia apropiacionista. Por ejemplo, su obra “Various Small Fires” (1964) ha sido “reescrita” por autores como Bruce Nauman (1969), Jonathan Monk (1969), Lucas Batten y Jonathan Sadler (2003), Thomas Galler (2009), Scott McCarney (2010), Doro Boehme y Eric Baskauskas (2010) y Marcella Hackbard (2010), generándose con ello, un movimiento de apropiacionionismos y resignificaciones que se cierra, al menos temporalmente, con “Various Small Shipwreck… and big Fires” (2016) de autoría propia.El objetivo del presente texto, es el de analizar dichas obras y sus relación con “Various Small Fires”, tomando a Ed Ruscha como fundador de discursividad, y al libro en sí, como icono para la memoria colectiva de los amantes de este género artístico y para la historia del hombre en general. Un análisis que nos ayudará a visualizar cómo algunos artistas bajo la figura del replicante han rehecho el estilo ruschiano para la construcción de nuevos discursos que, inevitablemente refractan, nuestras actuales prácticas de creación y producción editorial en un mundo cada vez más globalizado y dominado por los medios de comunicación masiva. Appropriationism and reinterpretations of the artwork “Various small fires” of Ed RuschaFor over fifty years, the artist’s books of Ed Ruscha have generated an appropriationist trend around the world. For example, his work “Various Small Fires” (1964) has been “rewritten” by authors such as: Bruce Nauman (1969), Jonathan Monk (1969), Luke Batten and Jonathan Sadler (2003), Thomas Galler (2009), Scott McCartney (2010), Doro Boehme and Eric Baskauskas (2010) and Marcella Hackbard (2010), etc. All of them have generated an appropriationist movement and resignifications which is closed, at least temporarily, with “Various Small Shipwreck ... and big Fires” ( 2016) of own authorship. The objetive of this text is to analyze these works and their relation to “Various Small Fires”, taking Ed Ruscha as founder of discourses, and the book itself, as an icon for the collective memory of lovers of this artistic genre and our history, too. Aso, this analysis will help us visualize how some artists under the figure of replicant have remade the style of Ruscha for the construction of new discourses that, inevitably, refracted our current practices of creating and publishing in an increasingly globalized world dominated by mass media.